Explicitly integrating institutions into bioeconomic modeling - Swallow, Kimberly A.; Swallow, Brent M. (International Food Policy Research Institute, 2015)
Bioeconomic models can provide powerful insights into the interactions between people and the natural ecosystems on which they depend. For example, bioeconomic models of fisheries have long been used to provide early warnings about the sustainability of harvest levels or the impacts of new technologies. Less progress has been made in explicitly incorporating inter-agent interactions and institutions in bioeconomic models. This paper offers guidance to future bioeconomic modelling efforts through a review of the ways that institutions are or could be explicitly integrated into bioeconomic models.